(untitled) (Revista Argentina de Musicología, 2018)
This article focuses on three books published by the author of this text between 1995 and 2015: Música latinoamericana y caribeña (Havana, 1995), co-authored with Zoila Gómez García and Historia de la música en España e Hispanoamérica, vol. 6, XIX (2010) and vol. 8, XX (2015), together with Consuelo Carredano, both edited in Madrid. It lists the objectives that guided these works and their main results, proceeding with some reflections about the unequal availability of sources in different countries or areas; the fragmented historiographical knowledge about the communities of indigenous and Afro-descendant peoples; the lack of articulation and insufficient transversality between areas that are still compartmentalized —historical music, ethnomusicology and popular musicology— and the need for the combination of different strategies and theoretical-methodological assumptions, in work teams that allow transversality, articulation and analysis of realities interrelated or juxtaposed in the academic and the popular in extensive and distant territorial spaces. Despite these and other limitations, it is important to have publications of this type for teaching in music and the humanities and for the dissemination of knowledge in general, as well as to encourage specialized studies.